2020
DOI: 10.2147/jbm.s254168
|View full text |Cite
|
Sign up to set email alerts
|

<p>Demographical Pattern of Blood Donors and Pre-Donation Deferral Causes in Dhahran, Saudi Arabia</p>

Abstract: Background: Understanding the demographic features of blood donors is important for identifying the donor structure and guiding the recruitment and retention strategies of donors. This study was aimed to determine the demographic characteristics of blood donors, the types of donation drives, and the frequency and reasons for pre-donation deferral in our population. Methods: This cross-sectional study included data analysis of all prospective blood donors presenting themselves for donation at the Blood Bank of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 37 publications
4
12
0
Order By: Relevance
“…The highest frequency of young donors in the current study might be due to over concentration on the selection of students’ donors. The finding was similar to studies found in Madagascar 17 and Saudi Arabia 18 which reported that most of the donors were the youngest age groups. The least donors were found in >50 years old age group.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The highest frequency of young donors in the current study might be due to over concentration on the selection of students’ donors. The finding was similar to studies found in Madagascar 17 and Saudi Arabia 18 which reported that most of the donors were the youngest age groups. The least donors were found in >50 years old age group.…”
Section: Discussionsupporting
confidence: 91%
“…Other researches done in the area demonstrated that blood donation practice was low. 25,33 The finding was similar to the studies conducted in Tanzania, 4 Egypt 34 and Saudi Arabia, 18 but, contradicted to a study conducted in India where the voluntary blood donors accounted for 87.75% of the donors. 35 The discrepancy might be attributed to difference in knowledge, attitude and practice of blood donation between the populations.…”
Section: Discussionsupporting
confidence: 65%
“…In one Saudi study that surveyed primary care patients, those in the age group (31‐50 years) had the highest donation rates (57%) 8 . A recent hospital‐based study also found that the age group (26‐35 years) had the greatest contribution to the donor pool (around 47%) 32 . One European study found that persons in the age group (30‐44 years) were more likely to have donated blood compared to their younger and older counterparts in cohorts recruited across 1994 and 2014.…”
Section: Discussionmentioning
confidence: 99%
“…8 A recent hospital-based study also found that the age group (26-35 years) had the greatest contribution to the donor pool (around 47%). 32 One…”
Section: Demographic Predictors Of Donationmentioning
confidence: 99%
“…17 However, blood transfusion in Saudi Arabia is essentially a hospital-based process, with the primary sources being from a combination of a growing number of voluntary non-remunerated donations and family members. 18 Although there are other sources, such as regional blood banks and the Saudi Red Crescent, there is a lack of communication between the blood banks, blood donors, hospitals and people in need. 19 Due to the growing demand for blood donors, the WhatsApp platform being the most useful app among Saudi people, and the lack of research related to this area, this study aims to measure the impact of WhatsApp on the blood donation process in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%